Xanthogranulomatous cholecystitis: A clinicopathological study from a tertiary care health institution - Kansakar, PBS; Rodrigues, G; Khan, SA (Kathmandu University Medical Journal, 2009)
Background: Xanthogranulomatous cholecystitis is an unusual and destructive form of chronic cholecystitis and is indistinguishable from other forms of cholecystitis which makes preoperative diagnosis and surgery difficult. Objectives: To review the demographic and clinical aspects of xanthogranulomatous cholecystitis; to study the possibility of preoperative diagnosis and to identify the causes for difficult surgery. Materials and methods: All cases histopathologically diagnosed as xanthogranulomatous cholecystitis over a period of six years from October 1999 to September 2005 at Kasturba Medical College Hospital, Manipal, India were included in the study. Data of the patients was collected retro and prospectively. Results: A total of 615 patients underwent cholecystectomy out of which 33 (5.2%) were diagnosed to have xanthogranulomatous cholecystitis. Ultrasound abdomen showed gallbladder wall thickening in 19 (57.5%) cases and gallstones in 32 (96.9%) cases. Thirty (90.9%) underwent open cholecystectomy. Gallbladder could be removed totally in 25 (75.6%) cases whereas five (15.2%) had to undergo partial cholecystectomy and in one patient, only cholecystostomy could be performed due to dense adhesions. Laparoscopic cholecystectomy was attempted in 11 patients but successful only in two patients with a conversion rate of 81.8%. Postoperative wound infection was seen in five (15.1%) patients and one (3%) had minor biliary leak which was treated conservatively. Histologically, xanthogranulomatous cholecystitis was associated with malignancy in one (3.03%) patient. There was no mortality. Conclusion: Clinical presentation of xanthogranulomatous cholecystitis was indistinguishable from chronic cholecystitis. Ultrasonography may reveal only non specific findings of calculi and thickened gall bladder wall. Hence preoperative diagnosis is unlikely. Cholecystectomy was usually difficult owing to dense adhesions of gallbladder and Calot’s triangle. Conversion rate of laparoscopic cholecystectomy is higher. Morbidity associated with surgery is significant. Key words: Xanthogranulomatous cholecystitis, Cholecystectomy, Malignancy doi: 10.3126/kumj.v6i4.1738 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 472-475